EFFECT OF AUDIT FEE, AUDIT TENURE AND AUDIT ROTATION ON AUDIT QUALITY AT PUBLIC ACCOUNTING FIRMS IN MEDAN CITY - Sagala, Nurul Aprilyani; Sari, Maya (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2022)
This research was conducted to achieve the following objectives: (1) Knowing and analyzing the effect of Audit Fee on Audit Quality; (2) Knowing and analyzing the effect of Tenure Audit on Audit Quality; (3) Knowing and analyzing Audit Rotation on Audit Quality; (4) Knowing and analyzing the effect of Audit Fee, Audit Tenure and Audit Rotation on Audit Quality. In this study, the authors take an associative approach, the primary data source. Data was collected using a survey method by distributing questionnaires to auditors working at the Public Accounting Firm in Medan City. The sampling technique used in this study is purposive sampling and has special criteria, the questionnaires that were successfully received were 35 questionnaires. The data analysis technique used in this research is descriptive statistics, multiple regression test, hypothesis testing, and coefficient of determination test. The results showed that partially Audit Fee and Audit Tenure had a significant effect on Audit Quality, Audit Rotation had no effect on Audit Quality. Meanwhile, simultaneously audit fee, audit tenure and audit rotation have a significant effect on audit quality.